The Impact of Corporate Governance Mechanisms on the Financial Performance of State-Owned Enterprises in Indonesia - Elvira Julianti; Niken Yuni Astuti; Henny Setyo Lestari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the impact of corporate governance mechanisms on the financial performance of State-Owned Enterprises (SOEs) in Indonesia. The governance variables analyzed include board size, female board representation, board independence, audit committee, firm age, and leverage. Using panel data from Indonesian SOEs, the results show that board size, female board representation, board independence, audit committee, and firm age do not have a significant effect on financial performance as measured by return on equity (ROE). In contrast, leverage is found to have a significant negative effect on ROE, indicating that higher debt levels tend to reduce equity returns. These findings suggest that, within Indonesian SOEs, financial structure plays a more prominent role in determining profitability than the corporate governance attributes examined in this study.